2003
DOI: 10.1029/2000jc000514
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of UV attenuation and colored dissolved organic matter absorption spectra from measurements of ocean color

Abstract: [1] The absorption of ultraviolet and visible radiation by colored or chromophoric dissolved organic matter (CDOM) drives much of marine photochemistry. It also affects the penetration of ultraviolet radiation (UV) into the water column and can confound remote estimates of chlorophyll concentration. Measurements of ocean color from satellites can be used to predict UV attenuation and CDOM absorption spectra from relationships between visible reflectance, UV attenuation, and absorption by CDOM. Samples were tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 57 publications
4
63
1
Order By: Relevance
“…Guo et al (2007) have observed a strong linear and inverse relationship of salinity and a CDOM in surface waters of the Yangtze River (YR) estuary in the ECS. This relationship appears to be consistent with various previous studies in other regions (Jerlov, 1968;Monahan and Pybus, 1978;Boss et al, 2001;Bowers et al, 2000Bowers et al, , 2004Binding and Bowers, 2003;Moon et al, 2006). A similar relationship together with the a CDOM -reflectance ratio relationship can therefore provide reliable estimates of salinity and CDOM in the focused YR estuary areas of the ECS using satellite ocean colour observations.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…Guo et al (2007) have observed a strong linear and inverse relationship of salinity and a CDOM in surface waters of the Yangtze River (YR) estuary in the ECS. This relationship appears to be consistent with various previous studies in other regions (Jerlov, 1968;Monahan and Pybus, 1978;Boss et al, 2001;Bowers et al, 2000Bowers et al, , 2004Binding and Bowers, 2003;Moon et al, 2006). A similar relationship together with the a CDOM -reflectance ratio relationship can therefore provide reliable estimates of salinity and CDOM in the focused YR estuary areas of the ECS using satellite ocean colour observations.…”
Section: Introductionsupporting
confidence: 82%
“…Coloured or chromophoric dissolved organic matter (CDOM), historically described as gelbstoff or yellow substance, is the main pool of absorbing substances in water and also plays a major role in various physical, chemical and biological processes (Johannessen et al, 2003;Twardowski et al, 2004). Coastal and estuary areas typically have higher and more variable abundances of these materials which originate primarily from humic substances of terrestrial origin transported to coastal seas through rivers and runoff from the land (Chester, 1990;Nelson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CDOM absorption spectra were corrected for instrument drift, fine particle scattering, and the difference between refractive indices for Milli-Q and estuarine and seawater using the following equation (Johannessen et al, 2003):…”
Section: Absorbance Fluorescence and Doc Measurementsmentioning
confidence: 99%